Android application for capturing personal data on name card using OCR - Tan, Woon Pang (2017)
The author was tasked to develop a user-friendly Android application (app) that can capture essential contact information on a business name card and store these information into a database for the user to view at his or her discretion. The author’s project timeline span the entire duration of Semester 1 and 2 for his Final Year Project (FYP), which is part of the prerequisite of completing the degree in Electrical and Electronic Engineering from Nanyang Technological University. This report aims to highlight what the author has learned and accomplished from completing his Android mobile app project. The author had to self-learn Java programming language to grasp the basics of utilizing object-oriented programming methodology to build a strong foundation to work in Android Studio’s IDE to build a client-side mobile app. Moreover, the author also has to learn server-side programming language PHP to handle the photo transmitted from the Android app to the server for several backend processing processes to extract and store the relevant contact information from the business name card photo. Moreover, the author also had to research and evaluate for viable free software’s or Application Programming Interface (API) (e.g. Optical Character Recognition (OCR), Natural Language Processing (NLP) and Name Entry Normalization function to determine multiple person’s name entry probability) on the commercial market that can extract free-form text with relatively high accuracy and disambiguate free-form text for unique data fields (e.g. Name, Address, Company Name and etc.) from a business name card to store into the respective designed database schema field. In addition, as an add-on to the project scope, the author also has designed a web interface on the server-side to reflect the stored database data fields into a presentable format where the user can view, add, edit and delete data entries at his or her discretion within the client-side app.